STRATEGI E-COMMERCE ERA MODERN: USER EXPERIENCE DAN AI CHATBOT SEBAGAI FAKTOR LOYALITAS PELANGGAN GEN Z - Saputra, I Gede Ega; Prawitasari, Putu Putri; Lestari, Ni Putu Eka; Suryanata, I Gusti Ngurah Putra (LP2M Universitas Bina Bangsa, 2025)
This study aims to determine the influence of User Experience, Artificial Intelligence Chatbot on Customer Satisfaction with Customer Loyalty as a mediating variable. The sample in this study is 112 consumers aged 15-29 years, domiciled in Denpasar and Shopee Application users. Using a quantitative approach, data was obtained through the distribution of questionnaires to respondents, using the Likert scale as a measuring tool. The results showed that independent variables, such as User Experience and Artificial Intelligence Chatbot, positively and significantly influenced the dependent variable, namely Customer Loyalty, directly. In addition, in the context of the influence of mediation, it was found that Customer Satisfaction plays a role as a mediating variable in the relationship between User Experience and Customer Loyalty. And also Customer Satisfaction plays a mediating variable in the relationship between Artificial Intelligence Chatbot and Customer Loyalty, with positive and significant results. This research can make a positive contribution to marketing literature and practically for Shopee companies need to consider the features in the application and web so that there are no bugs in the features, this affects the user experience so that users on the Shopee application and website feel the benefits of these features, so that increasing user satisfaction and customer loyalty will increase